Pengaruh Talent Management terhadap Employee Performance pada Sales People PT Indosat Ooredoo - Muhammad Yusuf Afandi (Jurnal Ilmu Manajemen, 2021)
Salespeople performance have a direct impact on organizational performance. Managing these talented salespeople to keep good work to achieve sales targets, contribute with extra effort to achieve the organization goal, be innovative and generate new ideas and not involve in any behavior that harms the organization well being is not easy. Effective and integrated talent management (TM) is needed to keep salespeople performance align with organizational goals. The purpose of this study is to confirm the effect of TM on employee performance. This study considers the mechanism of TM output (employee engagement) on the relationship between TM and employee performance. Path analysis and confirmatory factor analysis are employed by structural equation modelling partial least square (SEM-PLS) with 95 salespeople of PT. Indosat Ooredoo Tbk. as respondent.  The result shows that TM has a direct effect on employee performance (task performance, contextual performance, adaptive performance, counterproductive work behavior). Employee engagement as TM output is proven by the result that could mediate the relationship between TM and employee performance.